Depredation influences anglers’ perceptions on coastal shark management and conservation in the United States Gulf of Mexico - Prasky, Evan Gerald; Drymon, J. Marcus; Karnauskas, Mandy; Anderson, Alena Q.; Gibbs, Sarah L.; Grabowski, Jonathan H.; Jargowsky, Amanda E.; McAree, Danielle M.; Osowski, Ana R.; Swinea, Savannah H.; Scyphers, Steven B. (Frontiers in Conservation Science, 2023)
Shark depredation, the partial or complete removal of a hooked species by a shark, is an increasingly pertinent human-wildlife conflict, particularly in countries with robust shark management initiatives in place. Recently, in the United States, anecdotal reports suggest a rapid and significant increase in shark depredation among recreational anglers. Several studies have begun to characterize aspects of shark depredation; however, the relationship between perceived increases in shark populations and anglers' views on shark management and conservation remains unclear. To address this deficiency, we implemented a Gulf of Mexico-wide online survey to characterize the prevalence of depredation, as well as the impact of depredation on recreational reef fish anglers' fishing satisfaction and perceptions of shark management and conservation. Our findings confirm that depredation is widespread across the Gulf of Mexico, with similar depredation rates reported across the five states. However, most anglers reported that they have not changed their fishing behaviors in response to depredation. Generally, anglers who have experienced depredation believe that shark populations should be either maintained or reduced, and most attribute increases in depredation to regulations to protect sharks. Studies like this one are imperative for understanding how anglers view shark populations and the regulations in place to manage these species.